The association between obese patient’s behavioural practices and severity of obesity among obese patient attending clinic at Eku Baptist Government Hospital, Delta State, Nigeria - Uwaka, Obiajulu E.; Ezemenahi, Isioma S.; Uzoma, Ifunanya G.; Onyechere, Jennifer C.; Otutu, Michael O. (International Journal Of Community Medicine And Public Health, 2025)
Background: Over the last two decades, the rate of obesity has rapidly increased across the developing world and behavioral practices (dietary habits, alcohol intake, smoking, physical inactivity) play important role in its development and management. Reducing the negative health impact of obesity requires an understanding of the connection between behavioral patterns and the severity of obesity. This study therefore sought to assess the relationship between obese patient’s behavioural practices and severity of obesity. Methods: This was a hospital based, cross-sectional descriptive study carried out at the general out-patient department of Eku Baptist government hospital, between May 2015 and July 2015. The chi-square test was used to test for the degree of association between categorical variables and the level of significant was set at p<0.05. Results: A total of 265 obese individuals who met the inclusion criteria were selected for this study, with females accounting for 205 (77.4%) and males 60 (22.6%) of respondents, giving a male:female ratio of 1:3.3. Most respondents-206 (77.7%) belonged to class 1 obesity, 45 (17.0%) belonged to class 2 while class 3 obesity accounted for 5.3% of the study population. This study showed that the relationship between severity of obesity, excessive alcohol consumption, and poor dietary habit were statistically significant while for physical inactivity and cigarette smoking were statistically not significant. Conclusions: By identifying the specific behavioural practices that contribute to the severity of obesity, healthcare providers and policymakers can design targeted programs to promote healthy behaviours and reduce the burden of obesity.